2019
DOI: 10.1016/j.jtho.2019.08.677
|View full text |Cite
|
Sign up to set email alerts
|

MA21.06 Preliminary Phase 1 Results of U3-1402 — A Novel HER3-Targeted Antibody–Drug Conjugate—in EGFR TKI-Resistant, EGFR-Mutant NSCLC

Abstract: 7% Other. 1683 (66%) chose the requesting/treating track (50% government, 42% academic, 8% other). 61% reported most patients in their country do not receive molecular testing, with the lowest rates in Latin America/Other (p<0.0001). 39% were not satisfied with the conditions of molecular testing in their country. Indications for requesting testing included: adenocarcinoma (89%), never-smoker (61%), female (57%), and young (54%) (variable by region, p<0.0001). 99% ordered EGFR, 95% ALK, 84% PDL1, 79% ROS1, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Patients in the dose escalation received 3.2 mg/kg to 6.4 mg/kg HER3-DXd IV Q3W, which was guided by a Bayesian logistic regression model following the Escalation with Overdose Control (EWOC) principle. In the dose expansion part, patients in Cohorts 1 and 2 received the RDE of 5.6 mg/kg HER3-DXd IV Q3W (40); patients in Cohort 3 were randomized 1:1 to receive the RDE (Cohort 3a), or an uptitration of HER3-DXd (Cohort 3b). Two formulations were dosed in this study: frozen liquid drug product and lyophilized drug product.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the dose escalation received 3.2 mg/kg to 6.4 mg/kg HER3-DXd IV Q3W, which was guided by a Bayesian logistic regression model following the Escalation with Overdose Control (EWOC) principle. In the dose expansion part, patients in Cohorts 1 and 2 received the RDE of 5.6 mg/kg HER3-DXd IV Q3W (40); patients in Cohort 3 were randomized 1:1 to receive the RDE (Cohort 3a), or an uptitration of HER3-DXd (Cohort 3b). Two formulations were dosed in this study: frozen liquid drug product and lyophilized drug product.…”
Section: Methodsmentioning
confidence: 99%
“…U3-1402 is an antibody-drug conjugate (ADC) developed by Daiichi Co., Ltd., which consists of patritumab acting on HER3 antibodies and the cytotoxic drug DX-8951 (Exitecan, a topoisomerase inhibitor). U3-1402 is effective against different drug resistance mechanisms against EGFR-TKIs, as demonstrated in phase I trial results published in 2019 (200). Another phase I study included 57 patients with EGFR-TKI resistance.…”
Section: Treatments Available After the Development Of Osimertinib Re...mentioning
confidence: 98%
“…[43][44][45][46] Although there was no effect on PI3K/Akt signaling, a HER3-DNA topoisomerase inhibitor ADC triggered apoptosis of tumor cells in a mouse model of EGFR TKI-resistant NSCLC. 47 Similarly, a HER3-monomethyl auristatin F(MMAF) ADC was able to overcome trastuzumab resistance in HER2-positive MBC cells in xenografts. 45 These preclinical results suggest that HER3-specific ADCs may represent a promising option for overcoming therapeutic resistance in cancer cells, particularly in those that overexpress HER3.…”
Section: Anti-her3 Antibodies and Antibody Drug Conjugates (Adc)mentioning
confidence: 99%
“…45 These preclinical results suggest that HER3-specific ADCs may represent a promising option for overcoming therapeutic resistance in cancer cells, particularly in those that overexpress HER3. 47 Early clinical trials have reported promising results thus far in patients with either HER-3 overexpressing breast cancer or resistant EGFR-mutant NSCLC who were treated with a HER3-DNA topoisomerase inhibitor ADC (patritumab deruxtecan/HER3-DXd). 48,49…”
Section: Anti-her3 Antibodies and Antibody Drug Conjugates (Adc)mentioning
confidence: 99%